Molecular cloning sequencing purification of stem bromelain from Ananas comosus - Amid, Azura; Yusof, Faridah (2010)
OBJECTIVE The objectives of this project are:  To clone stem bromelain from pineapple  To sequence the cloned bromelain gene  To study the stem bromelain characterization  To express the bromelain gene in the expression vector  To purify the expressed bromelain